Enabling Cape Verde to Perform Total Hip Replacement: Cost-Benefit Study - Nunes, Andreia Mercier (2018)
Introduction: Cape Verde is a middle-income country benefiting from a health agreement with Portugal. The purpose of this study is to conduct a cost-benefit analysis on the enablement of Cape Verde to perform total hip replacement.Material and Methods: We assessed records from the Orthopaedic Department of Baptista de Sousa Hospital and the Portuguese Directorate-General of Health regarding hip fracture with indication for total hip replacement and hip arthritis cases evacuated to Portugal. We also analysed the direct costs of the treatment, and hypothesised the costs of performing total hip replacement in Cape Verde. We then conducted a cost-benefit analysis.Results: From 2011 to 2016, 126 patients (135 hips) would have indication for total hip replacement if it was possible to do it in Cape Verde. The performance of the procedure in Cape Verde would have resulted in a global benefit of €80 644.08, and a benefit of €597.36/per patient.Discussion: Our analysis indicates that the enablement of Cape Verde to autonomously perform total hip replacement on patients with hip fracture and arthritis would have a positive financial return. Total costs were underestimated due to the impossibility to calculate indirect costs. Enabling Cape Verde to perform total hip replacement would provide the recommended treatment for patients and reduce the socio-psychological impact of evacuation. Conclusion: Enabling Cape Verde to perform total hip replacement would represent an expense reduction, and an improvement of the country’s quality of healthcare and autonomy.